2015
DOI: 10.1007/s11010-015-2406-2
|View full text |Cite
|
Sign up to set email alerts
|

A carbazole alkaloid deactivates mTOR through the suppression of rictor and that induces apoptosis in lung cancer cells

Abstract: Non-small cell lung cancer (NSCLC) is known to be a difficult cancer to treat because of its poor prognosis, limited option for surgery, and resistance to chemo or radiotherapy. In this study, we have demonstrated that suppression of rictor expression in A549 and H1299 NSCLC cells by mahanine, a carbazole alkaloid, disrupted constitutive activation of mTOR and Akt. Mahanine suppression of rictor gene expression and consequent attenuation of its protein expression affected the inhibition of mTOR (Ser-2481) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…These results established the potential of M. koenigii as an anticancer agent in vitro [11]. Additional evidence for the anticancer activity of M. koenigii has been obtained from rodent cancer cell lines, as well as different in vivo cancer models [12][13][14][22][23][24]114,115]. In an early study, histopathological evidence showed that M. koenigii extract treatment generated a decline in neoplasms in the colon [85].…”
Section: Anticancer Activity (In Vivo and In Vitro)mentioning
confidence: 65%
See 2 more Smart Citations
“…These results established the potential of M. koenigii as an anticancer agent in vitro [11]. Additional evidence for the anticancer activity of M. koenigii has been obtained from rodent cancer cell lines, as well as different in vivo cancer models [12][13][14][22][23][24]114,115]. In an early study, histopathological evidence showed that M. koenigii extract treatment generated a decline in neoplasms in the colon [85].…”
Section: Anticancer Activity (In Vivo and In Vitro)mentioning
confidence: 65%
“…The bark is helpful in treating snakebites [17][18][19][20]. The essential oil extracted from M. koenigii leaves is reported to possess anti-oxidative, hepatoprotective [21][22][23][24], antimicrobial, antifungal [25][26][27], anti-inflammatory, and nephroprotective activities in animal models [28][29][30]. The medicinal properties of M. koenigii have been accredited to several chemical constituents of different carbazole alkaloids and other important metabolites, like terpenoids, flavonoids, phenolics, carbohydrates, carotenoids, vitamins, and nicotinic acid from different parts of the M. koenigii plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the loss of RICTOR in oocytes causes follicular apoptotic death, 54 while the deletion of RICTOR in osteoblasts inhibits osteoblast bone formation 114 . Furthermore, the suppression of RICTOR induces apoptosis in lung cancer cells 53 …”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is the process of programmed cell death, which can occur either through the extrinsic pathway, which is characterized as death receptor-mediated, 44 and the intrinsic pathway, which is influenced by members of the bcl family (bax and bcl-2) to act as pro- or anti-apoptotic factors depend on the regulatory proteins 45 . The activation of pro-apoptotic proteins, such as FOXO-1 46 , FOXO-3, 47 and PTEN, 48 and the inactivation of anti-apoptotic proteins, such as ILK, 49 MDM2, 50 NOS3, 51 mTOR, 52 and RICTOR,53, 54 leads to apoptosis.…”
Section: Introductionmentioning
confidence: 99%